The Effects of Acetazolamide on the Evaluation of Cerebral Hemodynamics and Functional Connectivity Using Blood Oxygen Level–Dependent MR Imaging in Patients with Chronic Steno-Occlusive Disease of the Anterior Circulation - Wu, J.; Dehkharghani, S.; Nahab, F.; Allen, J.; Qiu, D. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: Measuring cerebrovascular reactivity with the use of vasodilatory stimuli, such as acetazolamide, is useful for chronic cerebrovascular steno-occlusive disease. The purpose of this study was to evaluate the effects of acetazolamide on the assessment of hemodynamic impairment and functional connectivity by using noninvasive resting-state blood oxygen level–dependent MR imaging.MATERIALS AND METHODS: A 20-minute resting-state blood oxygen level–dependent MR imaging scan was acquired with infusion of acetazolamide starting at 5 minutes after scan initiation. A recently developed temporal-shift analysis technique was applied on blood oxygen level–dependent MR imaging data before and after acetazolamide infusion to identify regions with hemodynamic impairment, and the results were compared by using contrast agent–based DSC perfusion imaging as the reference standard. Functional connectivity was compared with and without correction on the signal by using information from temporal-shift analysis, before and after acetazolamide infusion.RESULTS: Visually, temporal-shift analysis of blood oxygen level–dependent MR imaging data identified regions with compromised hemodynamics as defined by DSC, though performance deteriorated in patients with bilateral disease. The Dice similarity coefficient between temporal-shift and DSC maps was higher before (0.487 ± 0.150 by using the superior sagittal sinus signal as a reference for temporal-shift analysis) compared with after acetazolamide administration (0.384 ± 0.107) (P = .006, repeated-measures ANOVA). Functional connectivity analysis with temporal-shift correction identified brain network nodes that were otherwise missed. The accuracy of functional connectivity assessment decreased after acetazolamide administration (P = .015 for default mode network, repeated-measures ANOVA).CONCLUSIONS: Temporal-shift analysis of blood oxygen level–dependent MR imaging can identify brain regions with hemodynamic compromise in relation to DSC among patients with chronic cerebrovascular disease. The use of acetazolamide reduces the accuracy of temporal-shift analysis and network connectivity evaluation.ACZacetazolamideBOLDblood oxygen level–dependent MR imagingDMNdefault mode networkSMNsensorimotor networkSSSsuperior sagittal sinusTmaxtime-to-maximum of the residue functionTStemporal-shift